2019
DOI: 10.3389/fpls.2019.01562
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenophora tritici–repentis in Tunisia: Race Structure and Effector Genes

Abstract: Tan spot is a destructive foliar wheat disease worldwide and caused by the ascomycete fungus Pyrenophora tritici-repentis (Ptr); it has become more frequent in Tunisia over the last decade. In this study, the virulence of 73 single-spore isolates, collected from durum and bread wheat fields during 2017-2018 growing season, was evaluated on four differential wheat genotypes. This was followed by polymerase chain reaction tests with specific primers for the effector genes ToxA, ToxB, and toxb (ToxB-homolog). Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 59 publications
2
51
0
2
Order By: Relevance
“…Further, races 1 and 2 are reported to be the predominant P. tritici-repentis races present in wheat growing areas in Canada (Lamari et al 1998;Lamari et al 2005;Aboukhaddour et al 2013), USA (Friesen et al 2005), Baltic States and Romania (Abdullah et al 2017) and South America (Gamba et al 2012;Bertagnolli et al 2019). In contrast, in North Africa, P. tritici-repentis populations in Morocco and Tunisia were reported to be mostly positive for ToxB (Gamba et al 2017;Kamel et al 2019). Kamel et al (2019) reported that whilst ToxA was only detected in 51% of isolates, ToxB was amplified in 97% of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, races 1 and 2 are reported to be the predominant P. tritici-repentis races present in wheat growing areas in Canada (Lamari et al 1998;Lamari et al 2005;Aboukhaddour et al 2013), USA (Friesen et al 2005), Baltic States and Romania (Abdullah et al 2017) and South America (Gamba et al 2012;Bertagnolli et al 2019). In contrast, in North Africa, P. tritici-repentis populations in Morocco and Tunisia were reported to be mostly positive for ToxB (Gamba et al 2017;Kamel et al 2019). Kamel et al (2019) reported that whilst ToxA was only detected in 51% of isolates, ToxB was amplified in 97% of the population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in North Africa, P. tritici-repentis populations in Morocco and Tunisia were reported to be mostly positive for ToxB (Gamba et al 2017;Kamel et al 2019). Kamel et al (2019) reported that whilst ToxA was only detected in 51% of isolates, ToxB was amplified in 97% of the population. The New Zealand populations of P. tritici-repentis screened in this study were isolated from symptomatic wheat leaves, with both necrosis and extensive chlorosis observed in the field indicating the isolates were capable of inducing chlorosis on all wheat cultivars sampled (Weith 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PCR was also performed to examine the frequencies of each of the three genes (ToxA, ToxB and toxB), but not for ToxC, which has not been cloned and sequenced, so that primers could not be designed for this gene. ToxA was present in 37 (51%) isolates, ToxB was present in 71 (97%) isolates with its homolog toxB present in 68 (93%) isolates (Kamel et al 2019). A subset of 22 isolates was also subjected to sequencing resolving sequence polymorphism in ToxA and ToxB/toxB (Kamel et al 2019).…”
Section: Genetics Of Sensitivitymentioning
confidence: 99%
“…ToxA was present in 37 (51%) isolates, ToxB was present in 71 (97%) isolates with its homolog toxB present in 68 (93%) isolates (Kamel et al 2019). A subset of 22 isolates was also subjected to sequencing resolving sequence polymorphism in ToxA and ToxB/toxB (Kamel et al 2019). (ii) In Australia, races 1 and 2 are the most predominant races, although races 5-8 are also common, which were rarely found in the Americas.…”
Section: Genetics Of Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation